2012
DOI: 10.1089/jop.2011.0147
|View full text |Cite
|
Sign up to set email alerts
|

Rebamipide Increases Mucin-Like Substance Contents and Periodic Acid Schiff Reagent-Positive Cells Density in Normal Rabbits

Abstract: Rebamipide is a possible candidate drug for treatment of cornea and conjunctival epithelial damage due to its mucin-like substance increasing action, for instance, in the treatment of dry eye disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…17 It is known that the application of topical rebamipide increases both the number of goblet cells and the level of mucin-like substances in the bulbar conjunctiva of rabbits, 18,19 promotes the proliferation of cultured rat conjunctival goblet cells, 20 and induces the mucin secretion from cultured conjunctival goblet cells of rats. 21 Application of rebamipide alleviates the inflammation in the small intestine through its anti-inflammatory effects and activation of the Wnt/β-catenin pathway.…”
Section: Introductionmentioning
confidence: 99%
“…17 It is known that the application of topical rebamipide increases both the number of goblet cells and the level of mucin-like substances in the bulbar conjunctiva of rabbits, 18,19 promotes the proliferation of cultured rat conjunctival goblet cells, 20 and induces the mucin secretion from cultured conjunctival goblet cells of rats. 21 Application of rebamipide alleviates the inflammation in the small intestine through its anti-inflammatory effects and activation of the Wnt/β-catenin pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, the increases in the action of conjunctival mucin for both ultrafine (Fig. 8) and microparticle 6) suspensions might have reached the maximal effect with rebamipide concentrations of 2% or less in the rabbits that were tested for the present study.…”
Section: Discussionmentioning
confidence: 89%
“…1,2) In the ophthalmologic field, a 2% rebamipide ophthalmic suspension (Mucosta ® ophthalmic suspension UD2%) is known to be effective for the treatment of dry eyes, 3,4) and, therefore, has been marketed in Japan for the treatment of this condition since January 2012. Rebamipide increases the mucin-like glycoproteins 5,6) and suppresses cytokine production in the cornea and conjunctiva, 7,8) which results in improvements in symptoms related to dry eyes.…”
mentioning
confidence: 99%
“…Now marketed in Japan, however, are diquafosol ophthalmic solution (Diquas Ophthalmic Solution 3%; Santen Pharmaceutical Co., Ltd., Osaka, Japan) and rebamipide ophthalmic solution (Mucosta ophthalmic suspension UD2%; Otsuka Pharmaceutical Co., Ltd., Tokyo, Japan). Both ophthalmic solutions induce mucin production 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…Rebamipide also exerts further effects on the ocular surface cells. Experiments have shown that rebamipide increases the amount of mucinlike substances in the conjunctival goblet cells and in keratoconjunctival epithelial cells in vitro and in vivo 2,6,7 . In addition, as a clinical topical agent rebamipide has been shown to increase the number of mucin-containing goblet cells 8 .…”
Section: Introductionmentioning
confidence: 99%